Classroom and School Predictors of Civic Engagement Among Black and Latino Middle School Youth. Issue 4 (13th June 2017) - Jagers, Robert J.; Lozada, Fantasy T.; Rivas‐Drake, Deborah; Guillaume, Casta
Abstract : This study used short‐term longitudinal data to examine the contributions of democratic teaching practices (e.g., the Developmental Designs approach) and equitable school climate to civic engagement attitudes, beliefs, and behaviors among 515 Black and Latino middle school students (47.9% male). Concurrent experiences of democratic homeroom and classroom practices, and equitable school climate were associated with higher scores on each civic engagement component. The relation between classroom practices and civic attitudes was more robust when school climate was seen as more equitable. Longitudinally, homeroom practices and equitable school climate predicted higher civic attitudes 1 year later. Discussion focuses on civic attitudes and future research on school experiences that support civic engagement among youth of color. Abstract : The title for this Special Section isPositive Youth Development in Diverse and Global Contexts, edited by Emilie Phillips Smith, Anne C. Petersen, and Patrick Leman